(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The article deals with the problem of psychological, medical and pedagogical training of future teachers for health-preserving activities in the outbreak of an emergency. Information is provided on measures to provide urgent psychological and health-preserving assistance to victims at the time of a natural disaster and at the stage of rehabilitation after exposure to emergencies resulting from natural disasters.